Histone H2A variants confer specific properties to nucleosomes and impact on chromatin accessibility. Issue 15 (26th June 2018) - Osakabe, Akihisa; Lorković, Zdravko J; Kobayashi, Wataru; Tachiwana, Hiroaki; Yelagandula, Ramesh; Kurumizaka, Hitoshi; Berger, Frédéric
Abstract: In eukaryotes, variants of core histone H2A are selectively incorporated in distinct functional domains of chromatin and are distinguished by conserved sequences of their C-terminal tail, the L1 loop and the docking domain, suggesting that each variant confers specific properties to the nucleosome. Chromatin of flowering plants contains four types of H2A variants, which biochemical properties have not been characterized. We report that in contrast with animals, in Arabidopsis thaliana H2A variants define only four major types of homotypic nucleosomes containing exclusively H2A, H2A.Z, H2A.X or H2A.W. In vitro assays show that the L1 loop and the docking domain confer distinct stability of the nucleosome. In vivo and in vitro assays suggest that the L1 loop and the docking domain cooperate with the C-terminal tail to regulate chromatin accessibility. Based on these findings we conclude that the type of H2A variant in the nucleosome impacts on its interaction with DNA and propose that H2A variants regulate the dynamics of chromatin accessibility. In plants, the predominance of homotypic nucleosomes with specific physical properties and their specific localization to distinct domains suggest that H2A variants play a dominant role in chromatin dynamics and function.